2007
DOI: 10.1212/01.wnl.0000264424.76759.e6
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of mild cognitive impairment in Kolkata, India

Abstract: In this first community-based study of mild cognitive impairment (MCI) from India, prevalence of the amnestic type is comparable with and that of the multiple domain type is less than the prevalence in developed countries. Variations in age, education, and gender specific prevalence of MCI of both types were encountered. The putative risk factors identified merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 34 publications
13
106
1
1
Order By: Relevance
“…Whereas, Shaji et al and Das et al reported hypertension and Diabetes Mellitus as a risk factors for dementia. 4,13 Reduced hearing [aOR 4.67 (1.15-18.91)] was a significant predictive factor of dementia in our study. Even though no causal link has been established between hearing loss and dementia, many epidemiological studies have shown hearing loss as a risk factor for developing dementia.…”
Section: Independent Risk Factors Of Dementiasupporting
confidence: 53%
See 1 more Smart Citation
“…Whereas, Shaji et al and Das et al reported hypertension and Diabetes Mellitus as a risk factors for dementia. 4,13 Reduced hearing [aOR 4.67 (1.15-18.91)] was a significant predictive factor of dementia in our study. Even though no causal link has been established between hearing loss and dementia, many epidemiological studies have shown hearing loss as a risk factor for developing dementia.…”
Section: Independent Risk Factors Of Dementiasupporting
confidence: 53%
“…Studies conducted in Kerala, Tamil Nadu and other parts of Northern India also reported increasing age as a nonmodifiable risk factor of dementia. 4,13,[16][17][18][19][20] Zhang et al reported the first time regarding the strong association of low education with dementia. 21 Similar association was also noted in the present study [OR 7.40 (2.70-20.34)].…”
Section: Independent Risk Factors Of Dementiamentioning
confidence: 99%
“…Available evidence indicates that the prevalence of MCI ranges from 7.7% to 42.0% depending on the age groups under consideration, the country where the study was conducted, and the diagnostic criteria used to make the diagnosis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1). The data from these studies indicate that MCI commonly occurs in older adults across different cultures, races, and ethnicities.…”
Section: Epidemiologymentioning
confidence: 99%
“…43 Moreover, amyloid-b deposition --a pathological hallmark of AD which can now be measured in vivo with amyloid imaging techniques --has been associated with vascular risk factors such as physical inactivity, higher plasma concentrations of cortisol, and hypertension. [44][45][46] The diagnosis of MCI has also been associated with several CVRFs; these include hypertension, 47,48 diabetes, 49,50 and increased cholesterol levels. 51,52 A recent large neuropathological study (5,715 cases) found that vascular pathology is more prevalent in patients with AD than in those with frontotemporal lobar degeneration, dementia with Lewy bodies, or Parkinson's disease dementia.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%